Comparative Transcriptome Analysis of the Effects of a Non-Insect Artificial Diet on the Nutritional Development of Harmonia axyridis - Tingting Zhang; Yinchen Yu; Jianyu Li; Li Zheng; Shiwei Chen; Jianjun Mao (Insects)
Artificial diets applied in the mass-rearing propagation of H. axyridis can improve reproductive ability by optimizing the feeding formula. This study used transcriptome data to investigate the effects of various artificial diets on the growth and development of H. axyridis. Results indicate that spawning increased with the low-fat and JH III-supplemented artificial diet (Diet 3). Furthermore, the highest glycogen content found in Diet 3 was significantly different from the other two groups. Triglyceride content decreased as adult feeding time increased in the three artificial diet groups, with the fastest decrease observed in the low-fat diet (Diet 2). Protein content increased gradually in the high-fat diet (Diet 1) group compared to the other treatment groups. The adults reared on low-fat artificial diets, when compared to those on artificial diets supplemented with juvenile hormones at the transcriptome level, were found to have upregulated genes enriched in ubiquitin-mediated proteolysis, ribosome biogenesis, and the hedgehog signaling pathway. In contrast, the genes upregulated in the latter group were enriched in oxidative phosphorylation, amino acid biosynthesis, and the metabolism of other amino acids. The results suggest that nutritional status significantly affects the growth and development of H. axyridis and has practical implications for the artificial feeding of natural pest enemies.